2015
DOI: 10.1007/s11596-015-1526-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of activated protein C on neurovascular unit in a rat model of intrauterine infection-induced neonatal white matter injury

Abstract: Activated protein C (APC), a natural anticoagulant, has been reported to exert direct vasculoprotective, neural protective, anti-inflammatory, and proneurogenic activities in the central nervous system. This study was aimed to explore the neuroprotective effects and potential mechanisms of APC on the neurovascular unit of neonatal rats with intrauterine infection-induced white matter injury. Intraperitoneal injection of 300 μg/kg lipopolysaccharide (LPS) was administered consecutively to pregnant Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…At the same time, the NVU can be directly disrupted by both of these diseases as well as systemic vascular conditions (Iadecola 2004;Girouard and Iadecola 2005;Zlokovic 2011;Deane et al 2012;Halliday et al 2016;Zenaro et al 2017). Experimental studies have generated evidence in support of the neurovascular hypothesis, identifying potential therapeutic targets that may prevent important neurodegenerative disease mechanisms (Iadecola 2004;Girouard and Iadecola 2005;Zlokovic 2011;Deane et al 2012;Carnevale et al 2012;Williams et al 2012;Jin et al 2015;Halliday et al 2016;Zenaro et al 2017).…”
Section: The Neurovascular Hypothesis Of Alzheimer Diseasementioning
confidence: 99%
“…At the same time, the NVU can be directly disrupted by both of these diseases as well as systemic vascular conditions (Iadecola 2004;Girouard and Iadecola 2005;Zlokovic 2011;Deane et al 2012;Halliday et al 2016;Zenaro et al 2017). Experimental studies have generated evidence in support of the neurovascular hypothesis, identifying potential therapeutic targets that may prevent important neurodegenerative disease mechanisms (Iadecola 2004;Girouard and Iadecola 2005;Zlokovic 2011;Deane et al 2012;Carnevale et al 2012;Williams et al 2012;Jin et al 2015;Halliday et al 2016;Zenaro et al 2017).…”
Section: The Neurovascular Hypothesis Of Alzheimer Diseasementioning
confidence: 99%
“…A Cochrane review on creatine for women in pregnancy for neuroprotection of the fetus, however, found no randomized controlled trials for inclusion . Some other molecules that were reported in animal experiments to alleviate fetal brain injury in inflammation‐driven preterm delivery when given to the mother include N ‐acetyl‐cysteine, activated protein C, erythropoietin, and i.v. immunoglobulin …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is one of the main causes of maternal morbidity and mortality, perinatal infection, and death. If an early intrauterine infection is not treated in a timely manner, fever can result in fetal tachycardia or bradycardia, decreased or increased fetal movement, fetal hypoxia, or even fetal death (11)(12)(13)(14). In the case of fetal hypoxia, the fetus suffers different degrees of asphyxia, which threatens its health and even life.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L I Discussionmentioning
confidence: 99%